ANATOMI DAN KUALITAS SERAT KAYU - Sissi Artistien; Y I Mandang (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
Since 1998. Indonesia has been importing wood items in shapes and species from other countries. This situation should not happen if we were able to use local wood species optimally. Wood anatomy of Hibiscus macrophyllus and Artocarpus horridus have been described for identification purposes and evaluation of the appropriate uses.Several particular important features for identification have been observed, as follows : (a) axialparenchyma diffuse in aggregates in Hibiscus macrophyllus. and axial parenchyma aliform in Artocarpus horridus, (b) Ray and fibers storied in Hibiscus macrophyllus and helical thickenings in ground tissue fibers in Artocarpus horridus. (c) mineral inclusions present in Hibiscus macrophyllus in the form of prismatic crystals and druses.The effect of height (upper. middle, and bottom trunks) and distance from the pith (core of the trunk) was significant on fiber dimensions of Hibiscus macrophyllus and Artocarpus horridus. However, such interaction did not bring about significant effect on the fiber wall thickness. About fiber length, it decreased with height levels from the bottom toward the top portion of trunk. Meanwhile, the fiber length increased from the pith toward the portion adjacent to the bark.The relationships between distance from the pith (X) and fiber length (Y) of Hibiscus macrophyllus can be described in three regression equations, as follows: Y = 749 + 1896X + 998X2, R1= 0.4505 (top portion), Y = 664 + 2419X - 1410X2, R2 0.4729 (middle portion), and Y= 1431 + 430X 270X - R1 - 0.0249 (bottom portion). likewise, the corresponding three regression equations for Artocarpus horridus are Y 1177 + 1537X - 927X2 R2- 0.2538 (top portion), Y - 1037 + 1207X - 314X2,R2 0.5519 (middle portion), and Y = 1480 + 969X 674X2, R2= 0.0625 (bottom portion).The fibers of Hibiscus macrophyllus and Artocarpus horridus have a medium quality. These species are therefore suggested for pulp and paper. Hibiscus macrophyllus is suggested too for light construction and mebel.